PENGANGKATAN ANAK DI DESA ADAT SUKAWANA: KEPENTINGAN ANAK VERSUS KEPENTINGAN ORANG TUA ANGKAT - sukmayasa, kadek; Bagiastra, I Nyoman; Pramana, Gede Pasek (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Generally, every married couple has the same desire to have a biological child. However, there are times when this wish does not come true for certain reasons. However, this desire is not completely dashed, because every family that does not have biological children can adopt children. Juridically, child adoption in Indonesia is regulated through Government Regulation Number 54 of 2007. Through this juridical basis, it is regulated that the implementation of child adoption can be carried out by following the provisions of Legislation and customary and customary provisions. The aim of this study is to analyze the implementation of appointment regulations in Indonesia which are carried out based on customs. This study was conducted using empirical legal research methods. The results of the study show that adoption is not only carried out for the child's interests, but there are other interests that are a factor in a family in Desa Adat Sukawana adopting a child. Regarding the technical implementation, in general the implementation of child adoption regulations in Indonesia has been implemented in the adoption of children based on customs in Desa Adat Sukawana. Adoption of children based on customs in Desa Adat Sukawana is regulated in Awig-awig. The procedure for adopting a child in the Sukawana Traditional Village is divided into 3 (three) stages, namely the preparation stage, the implementation stage, and the post-adoption stage. The study carried out contributes to knowledge in the field of Law, especially regarding the legal aspects of child adoption based on customs.